Comparison of DNA and RNA extraction efficiency from blood - SU Xinglei; LU Ping; PENG Junjie; WANG Zimin; SONG Ping; HAN Da (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To comprehensively evaluate the efficiency of different kits and methods for DNA and RNA extraction from blood samples.Methods·A total of 145 blood samples were collected, including those from patients with Alzheimer's disease (20 cases), fibrosis (5 cases), colorectal cancer (108 cases), and healthy individuals (12 cases). A column-based kit (Kit A) and a nucleic acid extraction instrument were used to extract genomic DNA (gDNA) from leukocytes in the blood. Cell-free DNA (cfDNA) and cell-free RNA (cfRNA) in plasma were extracted using five different kits (Kit B‒F), which employed either column-based (Kit B, E) or magnetic bead-based methods (Kit C, D, F). The extraction process of Kit B was optimized by increasing the plasma sample volume and extending the elution incubation time. Furthermore, this protocol was applied to extracting cfDNA from plasma samples of 100 colorectal cancer patients. Quantitative real-time PCR (qPCR) was used to quantify the extracted DNA and RNA, and the molecular yields were compared to evaluate the extraction efficiency. A comprehensive assessment was conducted, considering factors such as cost and operation time.Results·In gDNA extraction, although the the operation time was shortened by using the nucleic acid extraction instrument, the median number of DNA molecules extracted using Kit A (column-based method) was 25.36-fold higher than that obtained with the instrument (P<0.05). For cfDNA extraction, while the overall efficiency of the three kits (Kit B‒D) was similar, Kit B (column-based method) showed superior performance in low-concentration samples, with average DNA yields 4.24-fold and 1.18-fold higher than those of Kit D and Kit C (both magnetic bead-based). Optimization of Kit B's extraction protocol further improved cfDNA yield. When comparing three samples, the cfDNA yields from larger plasma input volumes was 3.98-fold, 2.38-fold, and 3.82-fold higher than those from smaller input volumes, respectively. The results of cfDNA extraction from 100 colorectal cancer patients indicated that this extraction protocol reliably extracted sufficient amounts of cfDNA from clinical samples. For cfRNA extraction, Kit E (column-based method) was widely recommended due to its high efficiency, convenience, and cost-effectiveness. The median RNA content extracted using Kit E was 5.01-fold higher than that of Kit F (magnetic bead-based method). Lastly, a comparison of the copy numbers of cfDNA and cfRNA in plasma revealed that the average copy number of cfRNA per milliliter of plasma was 27.65-fold higher than that of cfDNA.Conclusion·Kit A, Kit B, and Kit E show outstanding performance in leukocyte gDNA extraction, plasma cfDNA extraction, and plasma cfRNA extraction, respectively. However, although Kit E has advantages in extraction efficiency and cost, its safety requires further evaluation.